Developing and Validating E-Learning Module for Islamic Higher Education Digital Literacy in Preventing Hoax (EMODILPH) - Masykur, Ruhban; Irwandani, Irwandani; Aridan, Muhammad; Susilowati, Nur Endah; Soeharto, Soeharto (Universitas Islam Negeri Raden Intan Lampung, 2023)
The digital literacy curriculum in universities, especially Islamic universities, needs to be developed intensively to respond to the rapid exposure of hoax news among students. Therefore, this study aims to develop an e-module for digital learning and to investigate how this product can be implemented in a digital literacy curriculum model at Islamic universities. The Rasch measurement was used to assess fit validity and reliability criteria based on validator assessment and student responses. Many Facet Rasch Measurement was used to confirm validity and reliability from 4 different validators based on e-module development in phase 1 and phase 2 using 10-item criteria. A rating scale analysis was used to check validity and reliability according to 233 student responses and item category interactions. The e-module achieved fit validity and reliability. The e-module implementation showed students gave higher responses, 55% (agree) and 39% (strongly agree), if the e-module can help them with digital literacy for understanding hoax information. The bias interaction and the differential item functioning have been discussed in this study. The findings will provide initial knowledge in the development and implementation of e-modules for preventing hoaxes and will improve students' understanding of filtering information in the digital literacy curriculum.